Comparison of first year medical students' academic performance in blended and face-to-face learning strategies in physiology - Sibulo, Maria Carole Lisa C.
The University of Santo Tomas (UST) has adopted the use of a learning management system (LMS) called the Blackboard® (Bb) e-LeAP (electronic Learning Access Program), a program that offers courses online. Since its implementation in 2003, the university has been continuously encvouraging all colleges to use the system as a supplementary educational platform. The Department of Physiology, Faculty of Medicine and Surgery started utilizing the system since 2012. This study compared the blended learning approach with the traditional face-to-face learning approach in Physiology in terms of the academic performance of first year medical students. The study also determined the relationship of age, sex, and previous online learning experiences and the twodelivery modes with their academic performance. It is a quasi-experimental counterbalanced study that utilized a pretest-posttest design, where both groups experienced blended learning and lecturing as instructional approaches. All first year medical students enrolled at the Faculty of Medicine and Surgery taking Physiology were asked to participate in the study. Data analysis included crossover analysis of variance and paired t-test to compare the pretest-posttest scores of the students and linear regression analysis to determine the relationship of factors affecting the academic performance and learning variables. While both groups exhibited improvement in their posttests, results showed that students? performance scores in blended learning are significantly higher than in face-to-face learning. Crossover ANOVA also showed the significant carryover effect of blended learning to both lessons in Thermoregulation and Aviation. In terms of learner variables, male students performed better compared to females in both settings. Age and previous online learning experience did not have any relationship with students? academic performance in both strategies. Overall, there is a generally positive perception of students towards the blended learning course. Since blended learning course through the Blackboard e-LeAP supported higher improvement in students? academic performance, it is recommended that the university continue to explore the use of the Bb e-LeAP and explore how the university and faculty could help the students adapt it more easily. Subsequent research attempts with the same point of interest could also employ qualitative methods in order to explore more in-depth data.